Typology and Morphology The Building in the Area of Gunung- Gunung Street Malang City - Ratih, Nur (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2019)
Bergenbuurt area in Malang city has cultural heritage such as ancient buildings that have a colonial architectural style with the distinctive facade. Malang City Government itself has set this area as an area of cultural heritage so the existence, identity and image of the area could be maintained. This study is an advanced study of Antariksa et al (2004) conducted at the study area with a focus on the preservation of the buildings. The study showed some buildings that are considered to have the authenticity of a unique design and create the character of the area. This advanced study aims to identify the typology and morphology of the building that has been considered by previous researchers can create/influence the character / visual quality of the area. This study used a qualitative approach with descriptive methods of data analysis. Primary data obtained by field surveys on buildings based on the results of previous research. Building condition data from previous research is secondary data that is used to conduct study morphology of the building. Results of this study are expected to provide direction development of the area to preserve the visual character of the area.Â DOI: https://doi.org/10.26905/lw.v11i2.2834